Moving Forward: Prevention of Abuse of Older Women in the Post-Migration Context in Canada - Matsuoka, Atsuko; Guruge, Sepali; Koehn, Sharon; Beaulieu, Marie; Ploeg, Jenny (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2013)
Immigrants represent 28% of the Canadian population over 65, and older immigrants – more of them are women – now comprise the majority of the aging population in Canada’s large metropolitan cities. Despite ample research about abuse of older adults in general, few Canadian studies have focused on abuse of older immigrant women. This paper reports policy-relevant findings from a project that aimed to develop a shared program of research to prevent abuse of older immigrant women in Canada. The project involved a review of the literature on elder abuse and immigrant women, local meetings with key stakeholders in seven provinces, a public event in Toronto, and a two-day interdisciplinary symposium with provincial stakeholders. Two significant themes emerged from these activities: the value of bringing together professionals representing multiple disciplines and service sectors as well as older immigrant women and the need for changes in social policies to reduce older immigrant women’s vulnerability to abuse and support their resilience. This paper examines relevant social policy contexts and highlights the previously-overlooked implications of the ideology of familism within policies concerning prevention of abuse and the importance of intersectoral collaboration. Les immigrants constituent 28 % de la population canadienne de plus de 65 ans. Les immigrants âgés, dont la plupart sont des femmes, représentent désormais la majorité de la population vieillissante des grandes métropoles canadiennes. Malgré de multiples recherches sur les violences envers les personnes âgées en général, peu d'études canadiennes se sont concentrées sur les violences envers les immigrantes âgées. Ce document présente les conclusions d'un projet visant à élaborer un programme commun de recherche pour prévenir la violence envers les immigrantes âgées au Canada. Ce projet comprenait l'examen des publications existantes sur les violences envers les aînés et les immigrantes, des réunions locales avec les intervenants clés de sept provinces, un événement public à Toronto et un colloque interdisciplinaire de deux jours avec les intervenants provinciaux. Deux thèmes majeurs ont émergé au cours de ces activités : d'une part l'intérêt de rassembler des professionnels représentant de multiples disciplines et secteurs de services, et d'autre part les immigrantes âgées et la nécessité de faire évoluer les politiques sociales afin de réduire la vulnérabilité des immigrantes à la violence et de soutenir leur résilience. Ce document étudie les contextes sociopolitiques pertinents et met en avant les implications auparavant négligées de l'idéologie de la famille dans les politiques relatives à la prévention de la violence, ainsi que l'importance de la collaboration intersectorielle.